Vaginal leiomyoma in a bitch - SHRIVASTAVA, O P; CHANDRAPURIA, V P; CHAUDHARY, R B (The Indian Journal of Animal Reproduction, 2023)
An eleven-year-old Pomeranian bitch was operated for vaginal leiomyoma. An egg size lobulated ulcerated mass wasextirpated from the base and mucous membrane was sutured. Bitch made an uneventful recovery.
Keywords: Vaginal leiomyoma; bitch and surgical excision